All stages of the Palaearctic predaceous midge Palpomyia schmidti Goetghebuer, 1934 (Diptera: Ceratopogonidae) - Szadziewski, Ryszard; Golovatyuk, Larisa V.; Sontag, Elżbieta; Urbanek, Aleksandra; Zinchenko, Tatiana D. (Zootaxa, 2016)
All stages and the ecology of the Southern Palaearctic Palpomyia schmidti collected from the vicinity of the saline Lake Elton in Russia are described and illustrated. The morphology of larvae and pupae as well as the detailed ecology of the larvae are described for the first time. P. schmidti is a halobiontic biting midge, widely distributed in the steppes and deserts of the Palaearctic region. It is proposed that the Palpomyia schmidti group should include five Holarctic species. P. downesi Grogan & Wirth, 1979 from north-western North America is recognized as a new junior synonym of the Eastern Palaearctic P. tuvae Remm, 1972. New synonymy.